Long Noncoding RNAs: At the Intersection of Cancer and Chromatin Biology - Schmitt, Adam M. (Cold Spring Harb Perspect Med, 2017)
Although only 2% of the genome encodes protein, RNA is transcribed from the majority of the genetic sequence, suggesting a massive degree of cellular functionality is programmed in the noncoding genome. The mammalian genome contains tens of thousands of long noncoding RNAs (lncRNAs), many of which occur at disease-associated loci or are specifically expressed in cancer. Although the vast majority of lncRNAs have no known function, recurring molecular mechanisms for lncRNAs are now being observed in chromatin regulation and cancer pathways and emerging technologies are now providing tools to interrogate lncRNA molecular interactions and determine function of these abundant cellular macromolecules.